Otonomi Desa Dan Modernisasi Pemerintahan Desa - Dawud, Joni (Pusat Pembelajaran dan Strategi Kebijakan Talenta Aparatur Sipil Negara Nasional, 2007)
Indonesia hitherto is still looking for a right model in managing rural government auntonomy. Currently rural i s a spearhead and also a regency government’s spearhead in rural’s service and developments, thus is existence is needed and comprehended. However, rural government typically has not get recognizable position in National Administration System. Rural often recognized only as an institution of society, not an official institution, then again all matters dealt with are official matters. These problems must be elucidated before establising rural government in the future, therefore profesisionalism and accountabilities of a rural government could be assured.